Preferences of livestock owners for sharing the cost of brucellosis control in Tajikistan. (June 2020) - Ahuja, Vinod; Ward, David; Rajabov, Rukhshona; McLeod, Anni; Jackson, Ron
Abstract: In the context of significant public health benefits of brucellosis control and shrinking public resources for livestock vaccination, this paper considers the willingness of small ruminant livestock owners to pay for vaccination of their animals against brucellosis. The willingness to pay is estimated through a binary choice contingent valuation approach using data from a rural household survey specially designed for this purpose. The survey was conducted in southern Tajikistan, one of its poorest regions, in March 2009. The study used a non-parametric method for estimating the willingness to pay and a parametric (Probit) model for identifying determinants. The results show that households, including poor households, were willing to pay for continuing vaccination of their sheep and goats against brucellosis. Controlling for other attributes of willingness to pay, there was practically no correlation between willingness to pay and household asset level. This means both poor and rich alike are willing to pay for the service. On the other hand, the results also show that the willingness to pay was comparatively higher in households with relatively higher levels of education of adult females. This suggests that an awareness campaign targeted at female members of households would enhance the ownership and coverage of cost recovery programs and should form an integral part of any efforts towards introducing financial participation from sheep and goat owners for brucellosis vaccination. Highlights: Smallholder households are willing to share the cost of controlling brucellosis in small ruminants. Prior demonstration that bi-annual animal vaccinations were convenient and effective facilitated willingness to pay. Willingness to pay is not correlated with household asset level or small ruminant flock size. Vaccinated animals must be identified in order to monitor vaccination coverage. Comparatively higher education of adult females in households is correlated with higher willingness to pay.